2010
DOI: 10.1371/journal.pone.0012873
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity Study of Multiclade HIV-1 Adenoviral Vector Vaccine Alone or as Boost following a Multiclade HIV-1 DNA Vaccine in Africa

Abstract: BackgroundWe conducted a double-blind, randomized, placebo-controlled Phase I study of a recombinant replication-defective adenovirus type 5 (rAd5) vector expressing HIV-1 Gag and Pol from subtype B and Env from subtypes A, B and C, given alone or as boost following a DNA plasmid vaccine expressing the same HIV-1 proteins plus Nef, in 114 healthy HIV-uninfected African adults.Methodology/Principal FindingsVolunteers were randomized to 4 groups receiving the rAd5 vaccine intramuscularly at dosage levels of 1×10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
73
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 31 publications
12
73
0
1
Order By: Relevance
“…Some studies have shown that DNA alone is immunogenic in humans, albeit with low-magnitude responses as measured by ELISPOT and/or ICS (26,48,49). Use of Biojector does not seem to enhance immune responses to DNA in either humans or nonhuman primates, though few studies have directly compared standard intramuscular administration of DNA to Biojector in humans (49)(50)(51). In contrast, 7 of 11 individuals had an ELISPOT response to 3 doses of TBC-M4, though the mean magnitude of the response was modest.…”
Section: Figmentioning
confidence: 99%
“…Some studies have shown that DNA alone is immunogenic in humans, albeit with low-magnitude responses as measured by ELISPOT and/or ICS (26,48,49). Use of Biojector does not seem to enhance immune responses to DNA in either humans or nonhuman primates, though few studies have directly compared standard intramuscular administration of DNA to Biojector in humans (49)(50)(51). In contrast, 7 of 11 individuals had an ELISPOT response to 3 doses of TBC-M4, though the mean magnitude of the response was modest.…”
Section: Figmentioning
confidence: 99%
“…Specifically, the ability of prime-boost immunization with heterologous vectors to elicit robust cellular and humoral immune responses has been well documented (7,18,23). In this study, we first evaluated the potential of different prime-boost combinations involving replication-defective lymphocytic choriomeningitis virus (rLCMV), a genebased viral vector that elicits potent CD8 immune responses (17).…”
mentioning
confidence: 99%
“…Based on these relative successes obtained with preclinical experimental models, human trials have been initiated (17,26,28,43).…”
mentioning
confidence: 99%